Paths between Peace and Public Service : A Comparative Analysis of Public Service Reform Trajectories in Postconflict Countries - Blum, Jürgen René (Washington, DC: World Bank, 2018)
Building a capable public service is fundamental to postconflict state building. Yet in postconflict settings, short-term pressures often conflict with this longer-term objective. To ensure peace and stabilize fragile coalitions, the imperative for political elites to hand out public jobs and better pay to constituents dominates merit. Donor-financed projects that rely on technical assistants and parallel structures, rather than on government systems, are often the primary vehicle for meeting pressing service delivery needs. What, then, is a workable approach to rebuilding public services postconflict?